Behavior and Strength of Composite Columns under the Impact of Uniaxial Compression Loading - Hassooni, A. N.; Al Zaidee, S. R. (Engineering, Technology & Applied Science Research, 2022)
The Concrete Filled Steel Tube Column (CFST) is classified as a composite structural element. This type of column was adopted as the main loaded member in many buildings due to its excellent mechanical properties. CFST columns have high strength and ductility behavior, and they can sustain heavy loads with high performance. These led to their adoption in many countries. In the current study, the behavior and strength of CFST columns under the effect of axial compression load with parameters such as the diameter to thickness ratio and the height to diameter ratio were investigated. Strength carrying capacity and axial and lateral deformations with axial and lateral strains were explored. The test results showed that smaller heights within the same material gave higher strength capacity. The stiffness of the CFST is more than concrete and hollow steel section specimens’ due to its capability of high strength capacity with low displacement. Also, the composite action of CFST gave more stiffness.